Perbandingan Metode Penyelesaian Sengketa Tradisional dan Digital : Sebuah Pendekatan terhadap Optimalisasi ADR - Nabila Ikbal; Diana Setiawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Disputes usually occur due to differences in ideas, beliefs, values, needs, and goals, until finally people with different backgrounds cannot work together and cannot avoid disputes. Litigation is the most traditional dispute resolution which is a process in court using applicable law. Alternative Dispute Resolution is a concept of dispute resolution outside the court that prioritizes a win-win solution which is now integrated into the adjudication process as part of CDR or CADR. With a normative research method, which is sourced from secondary legal data, with primary legal materials, secondary legal materials, and tertiary legal materials, using qualitative data analysis methods by interpreting and describing questions contained in documents and laws and regulations. The results of this study indicate that the traditional dispute resolution method is a slow, protracted, and relatively expensive dispute resolution process, while the digital dispute resolution method in an approach to optimizing ADR has advantages in economic factors, scope factors and good relationship building factors.